Transferred plasma jet as a tool to improve the wettability of inner surfaces of polymer tubes - Prysiazhnyi, Vadym [UNESP]; Saturnino, Vinicius F. B. [UNESP]; Kostov, Konstantin G. [UNESP] (Taylor & Francis Ltd, 2017)
The wettability of the inner surfaces of vinyl, polyurethane, and silicone tubes was modified using an atmospheric pressure plasma jet operated in argon. A specific plasma jet configuration, transferred plasma jet, developed at Sao Paulo State University was utilized. It has been shown that it is possible to homogeneously alter the inner wall wettability of 1-m-long tubes, while providing safe plasma source usage for the operator. The water contact angle for three tube materials, i.e., vinyl, polyurethane, and silicone, changed from 98 degrees, 86 degrees, and 109 degrees to 55 degrees, 45 degrees, and 40 degrees, respectively.
Keywords: Plasma jet; polymer tube; polyurethane; silicone; tube inner surface treatments; vinyl